Parenteral administration medicines: recommendations of preparation, administration and stability - M. Gaspar Carreño; F. Torrico Martín; L. Novajarque Sala; M. Batista Cruz; P. Ribeiro Gonçalves; B. Porta Oltra; J. C. Sánchez Santos (Farmacia Hospitalaria)
Objective: To develop recommendations for the preparation of parenteral drugs (MAP), to assess the transferability of their preparation, from nursing units in the hospital ward to the pharmacy service (SF). Method: A table of stabilities of parenteral drugs included in the pharmacotherapeutic guideline was developed using the american and spanish guidelines. Information about MAP was collected (method of preparation, support, maintenance, validity, administration specifications and packaging) by consulting product technical sheets, pharmaceutical industries, literature review and databases. Results: After reviewing 209 drugs, a list of recommendations was developed. According to the data, MAP will be prepared as follows: 89 drugs will be prepared from SF, 62 drugs at nursing units because of its immediate administration requirement and 58 are already packed for its administration by the industry. Of these 62 drugs prepared a nursing units, 14 of them will be prepared in the following doses by the SF. Therefore, 48 drugs will be prepared at nursing units from the 209 parenteral drugs reviewed. Conclusions: A standardized method of preparation, storage, administration and validity of MAP was established by the SF. The preparation of MAP in the SF extends its shelf life, by considering physicochemical stability, level of risk and product vulnerability to microbiological contamination. The information provided will contribute to a reduction of errors associated with the preparation and administration of MAP.